The human 18S rRNA m6A methyltransferase METTL5 promotes tumorigenesis via DEPDC1 in lung squamous cell carcinoma - Yan, Yang; Fu, Jianjun (Frontiers in Oncology, 2025)
BackgroundN6-Methyladenosine (m6A) is one of the post-transcriptional modifications and abnormal m6A is critical for cancer initiation, progression, metastasis in Lung squamous cell carcinoma (LUSC). Ribosomal RNA (rRNA) accounts for most of the total cellular RNA, however, the functions and molecular mechanisms underlying rRNA modifications in LUSC remained largely unclear.MethodsHigh-throughput library screening identifies the key m6A regulator METTL5 in LUSC. Cell and animal experiments were used to identify that METTL5 promoted LUSC tumorigenesis to enhance DEP domain containing 1 (DEPDC1) translation via m6A modification.ResultsWe showed that the N6-methyladenosine (m6A) methyltransferase METTL5 was an independent risk factor in LUSC and was associated with poor prognosis of patients. Notedly, overexpression METTL5 promoted LUSC tumorigenesis in an m6A modification, while METTL5 knockdown markedly inhibited proliferation and migratory ability of tumor cells in vitro and in vivo. Mechanistically, METTL5 promoted LUSC tumorigenesis via m6a methyltransferase to increase the translation of DEPDC1.ConclusionOur results revealed that METTL5 enhances DEPDC1 translation to contribute to tumorigenesis and poor prognosis, providing a potential prognostic biomarker and therapeutic target for LUSC.